Out of the blue presentation out of the box management: diphtheria cases in Vadodara - Aiyer, Sheila; Sovani, Vishwas (International Journal Of Community Medicine And Public Health, 2024)
Diphtheria cases continue to be reported in India despite the national immunization programme although there has been an age shift to older children and adults in the recent outbreaks. This case study follows 17 patients of diphtheria treated at Sir Sayajirao General Hospital Vadodara between September 2022 and September 2023, their clinicoepidemiological profile and management. There were 4 females and 13 males, ages from 7 months to 11 years. While most cases had pharyngeal disease (grade 1), one case had nasopharyngeal disease (grade 2) and three had diseases for more than 3 days and extending to the neck (grade 3). Albert stain was reported positive in 10 cases and culture was not grown in any. Most cases were unimmunized or partially immunized. Mean duration of hospital stay was 9.3 days, longest being 35 days. Three cases died on day 2,4 and 21. In addition to crystalline penicillin, majority were administered Metronidazole and carnitine. DAT was used in doses of 40000, 60000 or 80000 IU uneventfully. When therapy is started based on clinical findings, adding metronidazole increases the spectrum of coverage and using levocarnitine protects against cardiomyopathy. In our series none of our cases died of cardiomyopathy. DAT was not involved in any of the deaths and was found safe and effective in all the cases. Diphtheria persists in different pockets in India and the only way of controlling it by increasing vaccine coverage.